Violations of Gricean Maxims in the TV Series You - Gledin Maulin; Thomas Joko Priyo Sembodo (Lexicon, 2021)
This research investigates the violations of Gricean maxims committed by the main characters in the TV series You Season 1, especially Joe Goldberg and Guinevere Beck. It focuses on how the two characters violate the maxims and the possible purposes behind each violation. Quantitative and qualitative methods were applied to the data analysis. The results show that 100 maxim violations were found in the first season of the series. The most frequently occurring violation is the violation of the quality maxim with 56 occurrences (56%), followed by the relation maxim (28%) and the manner maxim with (10%). The least occurring violation is the violation of the quantity maxim (6%). Joe Goldberg and Guinevere Beck tend to violate the maxims by being dishonest, saying irrelevant things, giving vague or obscure responses, and providing insufficient or unnecessary information. Several purposes of violations can be identified throughout the data, namely to avoid unwanted responses, avoid suspicion, make certain impressions, deceive, divert, persuade others, and relieve worries.